Resultados de los análisis palinológicos de los yacimientos LP-134, NA-20 y PN-106, Gran Coclé, Panamá - Moreno, Enrique; Murray, Katrina (Revista Española de Antropología Americana, 2007)
In this report we present the results of the palynological analyses of some samples taken in three archaeological ites of Gran oclé, to reconstruct the ancient landscape of the region and investigate if some of these ites was used like agricultural fields in Pre-columbian times.